PENGARUH BRAND IMAGE DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN LAYANAN SUBSCRIPTION VIDEO ONDEMAND (SVoD) NETFLIX - Sofianisa Rahmawati; Tandiyo Pradekso; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
In recent years, especially during the COVID-19 pandemic, Netflix's revenue has continued to decline throughout 2021 and 2022. On the other hand, Netflix, as the pioneer of SVoD services in the world, has implemented various strategies to build and maintain its good image. In addition, even though the price set is relatively higher, the amount of content available is greater than similar competitors and the price set is still within the range of the majority of spending by the Indonesian people in consuming SVoD shows. Nevertheless, Netflix has still not succeeded in becoming the main choice for the Indonesian people. This research aims to determine the effect of brand image and price perceptions on purchasing decisions for SVoD Netflix services This research uses a quantitative method with an explanatory type and is based on the concept of Customer-Based Brand Equity and the Model of Consumer Behavior. The sampling technique is in the form of non-probability sampling with a total sample of 100 respondents who are generation Z and millennials who live in Greater Jakarta and know Netflix. The results of this study using the Chi Square non-parametric statistical test tool succeeded in revealing a relationship between brand image and the decision to purchase Netflix services with a significance value of 0.000 < 0.050. Furthermore, different results occur in testing the effect of price perceptions on purchasing decisions, where there is no influence between the two variables indicated by a significance value of 0.119 > 0.050. Thus, this research shows that price is not the main issue that is considered by consumers in purchasing Netflix services, instead a good brand image is a consideration, so it is important for brands to continue to maintain a good image. This research is limited by variables that are used, as well as the age range and domicile of the respondents. Therefore, other variables and broaden background of the respondents can be used for the further research.